The impact of IFSA 2013 to the mudarabah-based products of Islamic Bank : a case study of Kenanga Investment Bank Berhad / Nor Mimi Afifah Mohd Shakri - Mohd Shakri, Nor Mimi Afifah (Academy of Contemporary Islamic Studies (ACIS), 2017)
The common principle that have been used by many Muslim society in Islamic finance and banking is mudarabah products. Currently in Malaysia, the Shari’ah Advisory Council (SAC) of Bank Negara Malaysia allocated the issues of mudarabah in a current account product in their resolutions. According to the SAC, there was a proposal from an Islamic banking institution to introduce a current account product based on mudarabah. This account is contrast from the wadi’ah current account because the payment of dividends to customers is at the sole discretion of the bank. In the mudarabah current account, customers were entitled to share some of the profits generated based on a pre-agreed profit sharing ratio upon the opening of the current account. After the implementation of IFSA 2013, mudarabah product have been classified as investment product effective from 30 June 2015. This study examines the objective of research to study the impact of IFSA 2013 to the mudarabah based product to ensure the return and income of Islamic bank remain its stability growth and sustain in this development country. This study is a qualitative research as involves of resources obtained from the library and also by interviews with the relevant authorities.